Auto(trans)formação permanente com professores(as) em contexto socioeducativo: educar(se) entre a coercitividade e a liberdade - Parigi, Camila da Rosa (2017)
Violence and youth are major themes of national debate. There is a growing daily questioning of the role of educational institutions and professionals working with youth, especially young people who experience violence and barbarism. Faced with these findings and questions about socioeducation, this master's research, inserted in the Training, Knowledge and Professional Development Line of the Graduate Program in Education of the Federal University of Santa Maria/RS, proposed to understand the implications, the limits and possibilities in the processes of permanent (trans)formation with the teachers in a school in the context of deprivation of liberty - CASE / SM. For that, it was necessary to know the Socio-Educational System, especially the context of the CASE / SM, in which through dialogic research-formative circles it was possible to identify implications, limits and possibilities in auto(trans) formative encounters with teachers school within the socio-educational unit. This research understood self (trans)formation as a necessary permanent process in which teachers constitute and constitute their practices. Through a qualitative research-training and case-study approach, the development of the research was based on the presuppositions of the political-epistemological proposal of the formative-investigative dialogic circles and the interpretation of official documents. The interpretations of the constructions were hermeneutics by the compression of magnification and construction of the knowledge. In this sense, historical and legal elements of education are presented within the socio-educational spaces that, together with the narratives of the teachers and the theorists that base this research, show possibilities for the construction of socioeducational practices and self-trans (trans)formative spaces taking as a perspective a socioeducational community that seeks the valuation of life. It has been found through studies of official documents and narratives with teachers that the socio-educational system is far from legally drawn projections. This research evidences the essential role of pedagogical and educational processes within the socio-educational unit by eminently transformative and humanizing aspects, as well as, it indicates the need to create spaces and times for dialogue, formation and construction of alternatives for conflicts with teachers and other professionals who work in the socioeducation. Faced with this, the potential of this research work is in the essential notes and discussions about education and young people in conflict with the law.